Guidance For Prospective Mothers And Its Implementation In Pre-Matrical Guidance At The Ministry Of Religious Affairs - Adih Amin; Indra, Hasbi; Handrianto, Budi; Hafidhuddin, Didin (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
Family as the main basis for children's education that will give birth to children expected by parents and become the successors of their parents' goodness. In reality, there are still many family problems that are seen in society, one of which is divorce. On average, it reaches a quarter of the two million marriage events in a year. Family education, which includes talking about mothers, is clearly described in the Qur'an. Family as the main basis for children's education that will give birth to children expected by parents and become the successors of their parents' goodness. In reality, there are still many family problems that are seen in society, one of which is divorce. On average, it reaches a quarter of the two million marriage events in a year. The approach in this study is qualitative research using a literature study method by referring to classical books and classical and contemporary interpretations. This research literature study also includes a field study by visiting one of the religious affairs offices. The purpose of this study is to overcome these obstacles. The government should pay attention to the budget so that education providers can provide the facilities needed for coaching.